Impact of Islamic Marketing and Cash on Delivery Services on Buying Interests on Tokopedia (District of Rappocini, Makassar) - Akib, Baso; Riskawati, Riskawati (Indonesian Journal Publisher, 2023)
The objective of this study is threefold: (1) to examine the influence of Islamic marketing on purchasing intention in the context of Tokopedia, (2) to investigate the effect of cash on delivery (COD) services on shopping intention in Tokopedia, and (3) to explore the impact of COD services on purchasing intention in Tokopedia. The present study employs a quantitative survey methodology. The data utilised in this study is classified as primary data. The collection of primary data is achieved through the utilisation of questionnaires and observations. The sampling technique employed in this study is purposive sampling, which involves selecting participants based on certain criteria. In this case, the criteria for participant selection are as follows: (1) individuals who are users of the Tokopedia platform; (2) individuals who possess knowledge of, or have previous experience using, Tokopedia features; and (3) individuals who have engaged in cash-on-delivery (COD) transactions when making purchases on the Tokopedia platform. The study utilised a sample size of 55 respondents, drawn from a population of 150,962 individuals. The sample size was determined using the indicator number formula, which was multiplied by a factor of 5. The data analysis procedures employed in this study involve the utilisation of double linear regression tests, which are conducted using SPSS Statistic 20 software for data processing. The findings of the study indicate that there is a somewhat favourable and statistically significant impact of Islamic marketing on the purchasing intention of consumers towards Tokopedia. Cash on delivery services (COD) exert a partially favourable and statistically significant impact on purchasing intentions within the context of Tokopedia.